Pharmacological preconditioning with gemfibrozil preserves cardiac function after heart transplantation - Benke, Kálmán; Szabó, Gábor (Scientific reports, 2017)
While heart transplantation (HTX) is the definitive therapy of heart failure, donor shortage is emerging. Pharmacological activation of soluble guanylate cyclase (sGC) and increased cGMP-signalling have been reported to have cardioprotective properties. Gemfibrozil has recently been shown to exert sGC activating effects in vitro. We aimed to investigate whether pharmacological preconditioning of donor hearts with gemfibrozil could protect against ischemia/reperfusion injury and preserve myocardial function in a heterotopic rat HTX model. Donor Lewis rats received p.o. gemfibrozil (150 mg/kg body weight) or vehicle for 2 days. The hearts were explanted, stored for 1 h in cold preservation solution, and heterotopically transplanted. 1 h after starting reperfusion, left ventricular (LV) pressure-volume relations and coronary blood flow (CBF) were assessed to evaluate early post-transplant graft function. After 1 h reperfusion, LV contractility, active relaxation and CBF were significantly (p < 0.05) improved in the gemfibrozil pretreated hearts compared to that of controls. Additionally, gemfibrozil treatment reduced nitro-oxidative stress and apoptosis, and improved cGMP-signalling in HTX. Pharmacological preconditioning with gemfibrozil reduces ischemia/reperfusion injury and preserves graft function in a rat HTX model, which could be the consequence of enhanced myocardial cGMP-signalling. Gemfibrozil might represent a useful tool for cardioprotection in the clinical setting of HTX surgery soon.
Gesehen am 11.04.2018